Interaction mechanism of pelargonidin against tyrosinase by multi‐spectroscopy and molecular docking. Issue 6 (16th March 2022) - Tao, Yanzhou; Chen, Rongda; Fan, Yangyang; Liu, Guiming; Wang, Meizi; Wang, Suqing; Li, Li
Abstract: The interaction mechanism of pelargonidin (PG) with tyrosinase was investigated by multi‐spectroscopy and molecular docking. As a result, PG had strong inhibitory activity on tyrosinase with the IC50 value of 41.94 × 10 −6 mol·L −1 . The inhibition type of PG against tyrosinase was determined as a mixed‐mode. Meanwhile, the fluorescence of tyrosinase was quenched statically by PG, and accompanied by non‐radiative energy transfer. The three‐dimensional (3‐D) fluorescence, ultraviolet‐visible spectroscopy (UV‐Vis) and circular dichroism spectroscopies (CD) indicated that PG decreased the hydrophobicity of the micro‐environment around tryptophan (Trp) and tyrosine (Tyr), which resulted in the conformational change of tyrosinase. In addition, fluorescence and molecular docking analysis indicated that PG bound to tyrosinase via hydrogen bonds (H‐bonds) and van der Waals force (vdW force). We herein recommended that PG might be a potential candidate drug for the treatment of melanin‐related diseases. Abstract : The interactions between pelargonidin with tyrosinase have been investigated. Through the pelargonidin structure figure, inhibition rate figure, fluorescence quenching figure and molecular docking figure composition of the graphical abstract. Results revealed that pelargonidin caused the fluorescence static quenching of tyrosinase protein. Van der Waals force or Hydrogen bonding force play major role in the binding process and the inhibition type of PG against tyrosinase was determined as a mixed mode.